Analisis Keterampilan Proses Sains Tentang Usaha dan Energi Peserta Didik Kelas X SMA Negeri 8 Pontianak - Risti Wulandari; Haratua Tiur Maria; Syukran Mursid (Departement of Mathematics Education, 2023)
This study aims to identify the profile of students' science process skills in answering questions about effort and energy at Senior High School 8 in Pontianak. The research employs a descriptive correlational survey method without a comparative group. The sampling technique used in this study was random sampling, involving a sample size of 65 students. The analysis of students' science process skills yielded a score of 64.48%, falling within the